Foreign private investment in Nigeria : proceedings of the twelveth Annual Conference of the Regional Research Units, organised by Research Department, CBN, at Hamdala Hotel Kaduna, Kaduna State, 1st - 5th September, 2003 - Nnanna, O. J.; Okafor, C. M.; Odoko, F. O. ([Abuja?] : Central Bank of Nigeria, 2003)
Proceedings of the twelveth Annual Conference of the Regional Research Units, organised by Research Department, CBN, at Hamdala Hotel Kaduna, Kaduna State, 1st - 5th September, 2003".
Includes bibliographical references.
oif 05/08/16
Loan
Keywords: Investments, Foreign; Investments; Nigeria